Chitosan–Pectin Composite Film as a Biodegradable Coating for Extending Banana Shelf Life - Nufus Kanani; Endarto Yudo Wardhono; Haroki Madani; Heri Heriyanto; Indar Kustiningsih; Wardalia Wardalia; Rusdi Rusdi; Rudi Hartono (World Chemical Engineering Journal, 2026)
Banana (Musa paradisiaca) is a climacteric fruit with a short postharvest shelf life due to rapid respiration, moisture loss, ethylene-induced ripening, peel browning, and microbial deterioration. Although synthetic plastic packaging can effectively reduce water loss, its non-biodegradable nature and potential to create unfavorable storage microenvironments encourage the development of sustainable bio-based coatings. This study investigated chitosan–pectin composite films as biodegradable coatings for banana preservation. Chitosan and pectin solutions were prepared using microwave-assisted extraction to improve dissolution homogeneity, followed by blending at various chitosan-to-pectin volume ratios. Glycerol was added as a plasticizer, and the resulting films were evaluated through weight loss analysis, visual observation, tensile testing, Fourier Transform Infrared spectroscopy, and Scanning Electron Microscopy. The results showed that coating application significantly reduced banana weight loss compared with uncoated samples. Synthetic plastic exhibited the strongest moisture barrier, but the chitosan–pectin formulation with a 50:50 ratio showed the best performance among bio-based coatings, reducing weight loss to 9.05%, 16.53%, and 19.44% on days 5, 10, and 15 of storage, respectively. Visual observation also indicated that the chitosan–pectin coating delayed peel browning and maintained better banana appearance up to 15 days. FTIR analysis confirmed intermolecular interactions between chitosan and pectin through shifts in O–H/N–H and C–N absorption bands, suggesting hydrogen bonding and electrostatic interactions. SEM images further revealed that pectin incorporation produced a more continuous and integrated film surface than chitosan alone. These findings demonstrate that chitosan–pectin composite coating, particularly at a 50:50 ratio, has strong potential as an environmentally friendly alternative to synthetic plastic for extending banana shelf life.